An exploration of role expectations of the clinical prosthetist. (February 2020) - Mackenzie, Renee L; Murphy, Gregory; Balasundaram, Arun Prasad; Morris, Meg E
Background: The role of the clinical prosthetist in healthcare has evolved substantially, and it is likely that expectations of the role have changed in recent times. Organisational Role Theory provides a framework for considering the expectations and behaviours of health professionals regarding their functions and roles. Objectives: The main objective of this study is to explore stakeholder consensus in role expectations of the clinical prosthetist in an Australian healthcare setting. Study design: Cross-sectional survey. Methods: The Prosthetist Role Expectations Scale was used to measure expectations and views of the roles of clinical prosthetists. The Prosthetist Role Expectations Scale has 72 items that form 11 subscales that describe prosthetist behaviour. It was distributed to six key stakeholder groups which included: prosthetists, prosthetic technicians, physiotherapists, medical rehabilitation specialists, orthotists and clients with limb loss. Results: Of the 1064 surveys distributed, 275 were returned. An additional 35 electronic responses were received, resulting in 299 complete data sets. A high level of consensus across the different stakeholder groups was found for 10 of the 11 subscales. In contrast, there were significant differences between groups for the 'Independent Prescription' subscale ( p ⩽ .05). Differences in expectations, as noted by individual Prosthetist Role Expectations Scale subscale items (7 of 72) may indicate that stakeholders perceive a prosthetist's role differently in select areas. Conclusion: There was broad agreement in expectations from stakeholders regarding the role of prosthetists in interdisciplinary functioning, research and communication related to prosthetic device provision and function. There were more varied expectations regarding prescription decisions, referral practices and clinician–client communication regarding emotional issues. Clinical relevance: It is important to understand the expectations that stakeholder groups have regarding the clinical prosthetist role in healthcare settings. Such information can guide health professional education and interprofessional practice and may reduce interpersonal and interprofessional conflict.